Hybrid Scenarios, Transmedia Storytelling, Expanded Ethnography - Domínguez Figaredo, Daniel (Revista de Antropología Social, 2012)
The transformation of social scenarios due to the impact of digital technologies, introduces new possibilities for ethnographic research. Once the initial approaches focused on the dichotomy of “physical-virtual spaces” have been overcame, it comes a stage of maturity that allows the ethnographers to open new avenues for conceptual and analytical methodology applied in techno-social scenarios. This article discusses the evolution of some key dimensions of ethnography according to the new social and epistemological framework. The discussion is based on the analysis of expanded practices that take place in the new techno-social spaces, defined as hybrid environments, where technologies are embedded in the physical life of the subjects. On the one hand, we consider the production of actions based on the assembly of ideas, meanings and objects through digital mediation devices. It is also analysed the transmedia component of the narratives that make sense to allow the experiments. Underlying the analysis, some elements are introduced for discussion on the scope of expanded ethnographic research, the influence of transmedia phenomenon in the notion of “field” and the methods for determining the significance through digital storytelling.